STRATEGI NAFKAH PENYADAP GETAH PINUS (Pinus merkusii) DI DESA PANJALU, KECAMATAN PANJALU, CIAMIS - Suhartono Suhartono; Ary Widiyanto (Fakultas Kehutanan Universitas Mulawarman, 2018)
Production of Pine sap is one of the main sources of income of Perum Perhutani. Therefore, its sustainability becomes very important and should give economic benefit to the tappers. The purpose of this study is to examine the amount of income obtained by sap tappers their household livelihood strategies. The results showed that the average of tappers income from this activity was between Rp 1.224.000- Rp 1.620.000. Factors affecting tappers income and tapping results are: 1) tapping ability, 2) amount of time and workday, 3) tapping period 4) number of trees able to be tapped per day, 5) land conditions, and 6) weather and season factors. Sap tapping was not the main source of income for respondents because their main occupations are majority farmers and breeders. They left tapping activity and back to farming activity during the rainy season, when the production of sap decreased.Keywords: sap, tappers, income, strategy